Joint Sub-Committee of the T.U.C., the Labour Party and the Co-operative Congress on the Government White Paper "A National Health Service" (minutes) - Labour Party (Great Britain) ; Co-operative Congress
1944-09-05 1944 1940s 6 pages PRIVATE AND CONFIDENTIAL 5th September, 1944 Joint Sub-Committee of the T.U.C., the Labour Party and the Co-operative Congress on the Government White Paper "A National Health Service" PRESENT: T.U.C. Mr. G.A. Isaacs, M.P. (Chairman) Mr. W.P. Allen Mr. J.W. Lowe Mr. J.L. Smyth Dr. H.B. Morgan, M.P. Labour Party Dr. S. Hastings Mrs. B.A. Gould Mr. Morgan Phillips Co-operative Congress Mr. R. Dinnage Mr. A. Ballard Mr. A.N. Lee Mr. C.W. Fulker The Sub-Committee considered the Government White Paper together with memoranda supplied by the constituent bodies and it was decided that a statement should be prepared embodying the views expressed. The statement in question is as follows:- 1. INTRODUCTION We were appointed as a Sub-Committee to examine and report back to our respective parent bodies on the Government White Paper "A National Health Service". As a result of detailed examination, we realise that the White Paper leaves many gaps and is not wholly on the lines which the Movement would desire but we are of opinion that it is a very big step forward and should be welcomed subject to the reservations made below. 2. SCOPE We think it is very important that there should be no departure from the White Paper proposal that every member of the community should be included in the scheme. Whilst appreciating that the White Paper allows a person covered by the scheme to pay for private treatment if he so desires, this should not in any way exempt such person from the financial provisions of the scheme. Similarly there should be no question of allowing any contracting out of the national scheme by individual contributors on the ground that they contribute to a voluntary hospital contribution scheme or on other such grounds. 3. AIM OF THE SCHEME A National Medical Service must ensure to every citizen the best that medical science can command for the prevention and cure of sickness. Whilst first class and fully co-ordinated treatment service must be built up, the prevention of illness must be the ultimate aim. Adequate records providing data for research are therefore very important and it is imperatively necessary that there should be a wide expansion of research work 292/847/2/10